The Effect Of Temperature And Filament Colour In 3D Printer To The Mechanical Strength And Impact Behaviour Of The Product - Muhamad, Faizal (2019)
3D printing or additive manufacturing (AM) based on fused deposition modelling (FDM) is currently the most widely available 3D printing platform. This method is a procedure of creating three dimensional solid objects from a digital file (CAD software). Additive process is the main conception in 3D printed. In this process, the object/product is created by laying down layers by layer of material until the object is created. Each of these layers of the process can be seen as a thinly sliced horizontal cross-section of the eventual piece. Even-though 3D printer offer various things of output product and can handle any level of complexity but there are many quality-related problems with 3D printing such as fragile product, delaminated FDM parts, low-resolution output materials and etc. To overcome this problem, this study is dedicated to investigate the effect of temperature and filament colour in 3D printing. Experimental method was select during this study. Four types of ABS filament colour which is yellow colour, brown colour, green colour and black colour was used. The level of temperature varies from 215°C and 245°C. In addition, two types of experiment was conducted in order to test mechanical properties for each specimen which is tensile test and charpy impact test in order to get the mechanical properties of the specimens. The 3D specimen was print by following ASTM standard D638-10 and ASTM D6110-04 for testing process. From the result finding, the maximum force is 902.8 N for black colour by using 225°C and its stress is 23.15 N/mm3. However the lowest force result comes from yellow colour at 215°C, this colour only archives at 399.29 N which is 55% lower than the maximum force value and the stress value is 10.24 N/mm3.